The role of person-job fit in the relationship between transformational leadership and job engagement - Bui, Hong T.M.; Zeng, Yolanda; Higgs, Malcolm (Journal of managerial psychology, 2017)
Purpose The purpose of this paper is to explore the relationship between transformational leadership and employees’ work engagement based on fit theory. The paper reports an investigation into the way in which employees’ perceptions of transformational leadership and person-job fit affect their work engagement. Design/methodology/approach To test the authors’ hypotheses, the authors performed structure equation modeling with maximum likelihood estimation on Mplus with bootstrapping proposed by Hayes (2009) with data from 691 full-time employees in China. Findings The results indicate that transformational leadership has as significant influence on employees’ work engagement as person-job fit in China. Moreover, employees’ perception of person-job fit is found to partially mediate the relationship between transformational leadership and employees’ work engagement. Research limitations/implications There is a possible bias arising from the use of cross-sectional data. However, certain methods were implemented to minimize it, including survey design and data analysis. Practical implications The paper proposes a number of practical implications for policy makers, HR managers and transformational leaders relating to issues associated with improving levels of employee engagement. Originality/value The study contributes to developing leadership and engagement theory by examining a previously unexplored mediator – person-job fit – in a neglected cultural setting. This study promises to open new research avenues in this area.